Quantitative observations of heterogeneities in Pseudomonas aeruginosa biofilms. - Stewart, P S (1993)
Heterogeneity in a Pseudomonas aeruginosa biofilm was quantified by measuring distributions of thickness in biofilm samples and a distribution of particle sizes in effluent samples. The mean steady-state thickness was approximately 33 microns, but individual measurements ranged from 13.3 to 60.0 microns. Particles exceeding 100 microns3 were observed in the reactor effluent. The results reveal a rough biofilm surface and indicate that most biomass detaches in the form of multicellular particles.